Chinese counterfeiting and piracy : real dangers to your health and our economy - Navarro, Peter (FTPress Delivers elements., 2010)
This Element is an excerpt from The Coming China Wars: Where They Will Be Fought and How They Can Be Won (ISBN: 9780132359825) by Peter Navarro. Available in print and digital formats. China's massive commercial piracy and counterfeiting industries: how they work and how they hurt you . Consumers may find it hard to feel sorry for fat cat corporations like Louis Vuitton or Disney when Chinese pirates knock off their luxury handbags or first-run movies. But Chinese counterfeiting and piracy are hardly limited to upscale baubles and Hollywood entertainment. And Chinese counterfeiting and piracy expose every one of us to extreme health and safety risks....